Microstructures and mechanical properties of brazed Al2O3/Cu joints with bismuth glass. Issue 13 (September 2019) - Chen, Haiyan; Ren, Xiaowei; Guo, Wei; Wan, Meiling; Shen, Zhikang; Liu, Xiaochao; Feng, Mingyang
Abstract: Alumina ceramics and copper were vacuum brazed using a bismuth-borate-zinc glass at temperatures between 660 and 720 °C for 20 min. The interfacial phases were characterized and the influence of brazing temperatures on microstructure of the joints were investigated. Shear tests of brazed joints under different conditions were also performed, and the joint fracture was observed and analyzed to determine the influence of brazing temperatures on the joint mechanical properties. Al2 O3 ceramic/Al2 O3  + glass phase/ZnAl2 O4  + glass phase/(Ni, Cu)O/Ni(s.s) + BiNi/copper was identified as the main structure of the Al2 O3 joints brazed with the glass. As the brazing temperature increased, the (Ni, Cu)O oxide layer in the joint was observed to thicken and extend to both sides gradually. The amount of BiNi formed in the Ni coating layer increased, and the scattered ZnAl2 O4 particles gradually grew. When the brazing temperature reached 700 °C, ZnAl2 O4 particles agglomerated on the alumina ceramic side, and glass permeated into the alumina base material. The shear strength of the joint first increased and then decreased with the increase of brazing temperature. The shear strength reached the maximum value of 21.1 MPa when brazed at 680 °C.